2012
DOI: 10.1074/jbc.m112.370064
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and β-1,6-N-Acetylglucosaminylation-initiated Aberrant Glycosylation of TIMP-1

Abstract: Background: Early TIMP-1 accumulation may impede cancer progression, and cancer cells need to reduce the antiproteolytic burden. Results: Early overexpression and later aberrant glycosylation of TIMP-1 support tumor progression. Conclusion: Concomitant overexpression of TIMP-1 and GnT-V directs accelerated tumor growth and cancer progression in vivo and in vitro. Significance: An answer to the debate on whether TIMP-1 is pro-or anti-oncogenic is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…Despite the increase in Timp1 expression in 4C11- and 4C11+ melanoma cell lines, high MMP activity was found in these melanoma cell lines (Figure 1D), suggesting MMP-independent functions of Timp1. Recently, Kim and coworkers showed that colon cancer cells have TIMP1 molecule bearing aberrant glycosylation, which impairs its efficient function as MMP inhibitor [33]. In fact, an increase in N- linked oligosaccharides was observed in melanoma cells derived from melan-a subjected to sequential cycles of deadhesion [10], reinforcing the idea that TIMP1 would confer tumor aggressiveness independent of its function on MMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increase in Timp1 expression in 4C11- and 4C11+ melanoma cell lines, high MMP activity was found in these melanoma cell lines (Figure 1D), suggesting MMP-independent functions of Timp1. Recently, Kim and coworkers showed that colon cancer cells have TIMP1 molecule bearing aberrant glycosylation, which impairs its efficient function as MMP inhibitor [33]. In fact, an increase in N- linked oligosaccharides was observed in melanoma cells derived from melan-a subjected to sequential cycles of deadhesion [10], reinforcing the idea that TIMP1 would confer tumor aggressiveness independent of its function on MMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are all heavily glycosylated proteins and known to be involved in resistance to chemotherapies in multiple cancer types [ 47 52 ], [ 16 , 53 , 54 ]. Moreover, as glycoproteins, the functions of TIMP1 and CLU were reported to be markedly influenced by altered glycans [ 55 57 ]. Nevertheless, previous studies rarely focused on the alterations of protein glycosylation during multi-drug resistance in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer cells are known to exhibit abnormal glycosylation of proteins 34, 35 . We used a glycosylation mutant that showed substantially reduced complex glycan modification and defective cell surface expression to model the impact ofSIGIRR ΔE8 in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%